2014
DOI: 10.1002/anie.201405334
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Deposition‐Crystallization Procedure for Highly Efficient Lead Iodide Perovskite Thin‐Film Solar Cells

Abstract: Thin-film photovoltaics based on alkylammonium lead iodide perovskite light absorbers have recently emerged as a promising low-cost solar energy harvesting technology. To date, the perovskite layer in these efficient solar cells has generally been fabricated by either vapor deposition or a two-step sequential deposition process. We report that flat, uniform thin films of this material can be deposited by a one-step, solvent-induced, fast crystallization method involving spin-coating of a DMF solution of CH3NH3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
914
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,377 publications
(946 citation statements)
references
References 42 publications
25
914
2
5
Order By: Relevance
“…Although spin-coating is an apparently simple and low cost deposition method, strong ionic interaction between metal cations and halogen anions commonly leads to the formation of inhomogeneous film morphology involved with poor surface coverage [106] , pillared structure [105] and non-uniform film thickness [99] .…”
Section: Perovskite Film Deposition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although spin-coating is an apparently simple and low cost deposition method, strong ionic interaction between metal cations and halogen anions commonly leads to the formation of inhomogeneous film morphology involved with poor surface coverage [106] , pillared structure [105] and non-uniform film thickness [99] .…”
Section: Perovskite Film Deposition Methodsmentioning
confidence: 99%
“…Anti-solvents to perovskite such as toluene, chlorobenzene are dripped during the spinning of precursor solutions. [97,106] [14,38,107] Depending on the solvent used in the precursor solution, antisolvent and dripping timing should be carefully controlled for highly efficient optoelectronic devices.…”
Section: Perovskite Film Deposition Methodsmentioning
confidence: 99%
“…During the second step, when approximately 15 seconds of the program remains, 100 µL of anhydrous chlorobenzene was applied on the spinning film with a hand held automatic pipette. This last step, known as the antisolvent method, has a large impact on film morphology and result in significantly better device performance [6][7][8] . It is, however, one of the steps that introduce a palpable degree of artisanship into the process.…”
Section: ~S3~mentioning
confidence: 99%
“…Xiao et al improved the reproducibility by improving the surface coverage of the perovskite layer on the scaffolds. 21 Wakamiya et al reported the importance of dehydrate PbI 2 . 22 We concluded that low reliability might also occur because of these defects.…”
Section: ¹2mentioning
confidence: 99%